Learning strategies in remote education: a study with undergraduate students in chemistry and biology (Research, Society and Development, 2021)
Remote learning, supported by media and technologies, has been growing in Brazil. The pandemic context made this teaching modality to be adopted as an emergency. Most students are not used to studying in person, which can interfere with their learning process. Thus, the objective was to identify the learning strategies used by undergraduate students in Chemistry and Biology during emergency remote classes in a General Chemistry course. Data collection took place through a Likert scale questionnaire. Data were treated quantitatively and analyzed qualitatively. The results show that the cognitive learning strategies most used by undergraduates were focused on writing down what they consider important in a given subject. Regarding metacognitive strategies (most used by participants), the most frequent were those aimed at reading and rereading texts carefully, trying to overcome the difficulty or to make sure they understand that content.